Why is Math Cheaper than English? Understanding Cost Differences in Higher Education - Steven W. Hemelt; Kevin Stange; Fernando Furquim; Andew Simon; John E. Sawyer (Institute of Labor Economics (IZA), 2018)
The private return to postsecondary investment varies widely by field, but the resources required by different fields are not well known. This paper establishes five new facts about college costs using novel department-level data. First, costs vary widely across field, ranging from electrical engineering (109 percent higher costs than English) to math (22 percent lower). Costs are generally higher in fields where graduates earn more and in pre-professional programs. Second, this pattern is explained statistically by differences in class size and faculty pay, though differences in production technology enable some fields to offset higher salaries with larger classes. Third, some STEM fields experienced steep declines in expenditures over the past fifteen years while others saw increases. Fourth, increases in class size and teaching loads alongside a shift in faculty composition toward contingent faculty explain these trends. Finally, online instruction is associated with a modest reduction in cost per student, but only for undergraduate instruction. Recent policy efforts to promote enrollment in high-earning fields will thus have important implications for postsecondary costs and the social return on investment in higher education.
Keywords: I21; I22; I23; 330; college costs; college major